ANALISIS TINGKAT AKURASI MODEL-MODEL PREDIKSI KEBANGKRUTAN UNTUK MEMPREDIKSI VOLUNTARY AUDITOR SWITCHING (Studi pada perusahaan manufaktur yang terdaftar di BEI) - Queenaria Jayanti; Rustiana Rustiana (Modus, 2015)
The aim of the study is to test the degree of accuracy of bankruptcy prediction modelsÂ to predict voluntary auditor switching, and at the same time the study also examinesÂ differencetiation in accuracy among the models. In this study, five bankruptcy predictionmodels are used, the model consist of Altman Zâ€-Score modification, Olson Y-score,Â Zmijewski X-Score, G-Score Grover, and Springate S-Score.The study consist of 432 companies are listing on Indonesia Stock Exchange duringÂ the years 2008-2011. The data are drawn from the Annual Financial Statements, IDXÂ Fact Book, and the Indonesian Capital Market Directory. The hypothesis is examined byÂ One Way ANOVA with level of significance 5%.Â The results indicate no differencing between the accuracy of bankruptcy predictionÂ among the models in predict the company undertake voluntary decision of switchingÂ auditors. However, the result shows that models Grover G - Score is the most high inÂ predicting of accuracy ratings. The implication of this study is for auditor to consider theÂ model to design the substantif test in audit activities.Â Keywords: Altman Zâ€-Score modification, Ohlson Y-Score, Zmijewski X-Score, G-ScoreÂ Grover, Springate S-Score, voluntary switching auditors.